PRMT5 Is Involved in Spermatogonial Stem Cells Maintenance by Regulating Plzf Expression via Modulation of Lysine Histone Modifications - Dong, Fangfang; Chen, Min; Chen, Min; Jiang, Lin; Shen, Zhiming; Ma, Longfei; Han, Chunsheng; Guo, Xudong; Gao, Fei (Frontiers in Cell and Developmental Biology, 2021)
Protein arginine methyltransferase 5 (Prmt5) catalyzes the formation of mono- or symmetric di-methylarginine in histones and non-histone substrates which has been demonstrated to play important roles in many biological processes. In present study, we found that Prmt5 was abundantly expressed in spermatogonia stem cells, and deletion of Prmt5 resulted in progressive loss of spermatogonia stem cells (SSCs) and male infertility. The proliferation of in vitro cultured Prmt5-deficient SSCs was abnormal, and the cell cycle was arrested in G0/G1 phase with a significant increase of apoptosis. The expression of PLZF was dramatically reduced in Prmt5-deficient SSCs and the levels of H3K9me2 and H3K27me2 was increased in the proximal promoter region of Plzf gene in Prmt5-deficient SSCs. Further study revealed that the expression of lysine demethylases (JMJD1A, JMJD1B, JMJD1C, KDM6B) was significantly reduced in Prmt5-deficient SSCs and the level of the permissive arginine methylation H3R2me2s was significantly decreased at upstream promoter region of these genes in Prmt5-deficient SSCs. Our study demonstrates that Prmt5 regulates spermatogonia stem cell development by modulating histone H3 lysine modifications.